Development of an Association Technique for a 3-Dimensional Minimum Configuration Multilateration System - Shehu Yaro, Abdulmalik; Sha'ameri, Ahmad Zuri (International Journal of Integrated Engineering, 2020)
Multilateration (MLAT) system estimates the position of an aircraft using time difference of arrival (TDOA) measurement estimated at ground receiving station (GRS) pairs with a lateration algorithm. In multiple aircraft scenarios, multiple TDOA measurements are estimated at GRS pairs. Thus, there is a need to group and associate the TDOA measurements according to each aircraft before the position estimation (PE) process with the lateration algorithm. In this paper, a multi-reference TDOA association (M-RETA) technique based on multiple referencing approach to TDOA estimation, its zero cyclic sum property, and nearest neighbor search approach is developed for a minimum configuration 3-D MLAT system. The performance of the M-RETA technique is determined considering a five aircraft flying configuration with an aircraft pair separation of at least 5.5 km in accordance with the Federal Aviation Administration (FAA) standard. Simulation result shows that the M-RETA technique association accuracy depends on the TDOA estimation error and separation between the aircraft. Simulation result shows that the M-RETA technique as on an average 88% probability of correct association.